Serum levels of interleukin 6, a potent myeloma cell growth factor, as a reflect of disease severity in plasma cell dyscrasias. - Bataille, R (1989)
Using a specific and very sensitive (1 pg = 1 U) bioassay, we investigated the presence of IL-6, a potent myeloma cell growth factor, in the sera of 131 subjects with plasma cell dyscrasias. 22 had monoclonal gammopathy of undetermined significance (MGUS), 13 had smoldering myeloma (SMM), 85 had overt multiple myeloma (MM), and 11 had plasma cell leukemia (PCL). Significant serum IL-6 levels were detected in only 3% of the MGUS/SMM group, but in 35% of the overt MM group and 100% of the PCL group. During overt MM, IL-6 was detected in 37% of the patients at diagnosis, 13% of those with stable MM, and 60% of those with fulminating disease. These data demonstrate that serum levels of IL-6, a potent myeloma cell growth factor in vitro, correlate with disease severity in plasma cell dyscrasias. Serial studies performed in 3 patients and correlative studies with labeling index in vivo in 25 patients have confirmed this concept. Taken together, this suggests that this cytokine is probably involved in vivo during the progressive phase of MM. Thus, anti-IL-6 or anti-IL-6 receptor antibodies could be useful as therapeutic agents at this stage of the disease.